Black Soldier Fly (Hermetia illucens) as a Potential Agent of Organic Waste Bioconversion - Listya Purnamasari; Himmatul Khasanah (Universitas Gadjah Mada, 2022)
The use of black soldier fly (BSF) as a bioconversion agent has become an emerging breakthrough in waste processing. Organic wastes, such as household waste and livestock manure, can be used as a growth medium for BSF larvae and converted into favorable products. The average composting time of BSF larvae is around 12– 15 days, which is faster than that of microbes or earthworms (4–5 weeks). BSF shows potential as a feed and food ingredient because it has a high nutritional content, such as enzyme, chitin, medium-chain fatty acid, and antimicrobial peptides, and can be used as a functional food ingredient. From an economical perspective, the short composting period and the role of BSF as a feed and food alternatives can benefit producers and consumers. The safety aspects of BSF utilization, including microbial safety, chemical safety, and environmental safety, warrant clarification to ensure BSF safety. However, some challenges arise regarding the use of BSF larvae (BSFL) as a bioconversion agent, such as for heavy metal residues, pesticide residues, pathogens, and antimicrobial gene transmission and residues that require the best composting strategy for mitigation. The environmental safety of organic waste treated with BSFL has a good impact; therefore, this strategy can be used to reduce global warming. Research must focus on effectively and safely enhancing the cultivation and processing of BSF and its applications as a functional food. In conclusion, BSF is a profitable alternative for organic waste bioconversion in developed and developing countries.